A co-simulation digital twin with SUMO and AirSim for testing lane-based UTM system concept - Wen, Zhang; Zhao, Junjie; Xu, Yan; Tsourdos, Antonios (IEEE, 2024)
The UAS (Unmanned Aircraft System) Traffic Management (UTM) System Concept of Operations (ConOps) is the first formal design reference document of the UTM system, ConOps aims to bring Class G Airspace into government regulation. However, it should be noted that there are still some shortcomings in ConOps that require further discussion. For example, there are concerns about operational rights, privacy rights, and the potential interference caused by high-rise buildings in urban core areas. The Lane-based UTM systems could potentially help in solving the above issues. The flight paths of Unmanned Aerial Vehicles (UAVs) in urban areas or other areas will interact with the road network, which can facilitate airspace traffic development. Ground traffic flow simulation is generally conducted on three levels: macroscopic, mesoscopic, and microscopic. Some of the commonly used car traffic flow simulation tools include Vissim, SUMO, and MATSim. However, UAV traffic simulation is mostly at a single level, and all of the current mainstream simulation software for UAV, such as Gazebo, AirSim, and Flight Gear, are microscopic-level analyses of UAV operations, lacking uniform management of drone traffic flow and operations. In addition, these UAV traffic simulation studies do not consider the city traffic and road network. In this context, a lane-based cosimulation UAV traffic simulation method is proposed in this study. The co-simulation architecture will be based on the highfidelity three-dimensional (3D) environment developed in the Unreal Engine, UAV simulation with AirSim, and twodimensional (2D) road network simulation with SUMO. A standardized and universal co-simulation architecture and communication interface to ensure interoperability, compatibility, and synchronization will be developed in this study. The lane-based co-simulation method will effectively leverage the road network simulation capacities to turn complex 3D space planning into simple 2D planning, it could reduce computational load and improve system efficiency. The 3D environment will also enhance the simulation capacities with its unique and high-fidelity simulation capacities. Overall, the proposed co-simulation method will support the Digital Twin development by interfacing several simulation tools, incorporating different communications, and adding realistic visualization, which could create unprecedented opportunities for software tool combinations.
Keywords: Three-dimensional displays; Roads; Microscopy; Urban areas; Computer architecture; Traffic control; Autonomous aerial vehicles